A multi-metal PtAgAu@CeO2 core–shell nanocatalyst with improved catalytic performance. (10th December 2018) - Zhang, Chao; Cheng, Xi; Guo, ZhenMei; Lv, Zhiguo
Abstract : A multi-metal PtAgAu@CeO2 core–shell nanocatalyst with improved catalytic performance is synthesized successfully. Abstract : A multi-metal PtAgAu@CeO2 core–shell nanocatalyst with improved catalytic performance is synthesized successfully. The scattered noble metal NPs could aggregate into one multi-metallic core due to the space limitation of the SiO2 layer during calcination treatment, thereby enhancing the interaction and co-catalysis effect between various metal NPs.